Effects of α + β phase deformation on microstructure, fatigue and dwell fatigue behavior of a near alpha titanium alloy. (October 2016) - Chandravanshi, Vivek; Prasad, Kartik; Singh, Vajinder; Bhattacharjee, Amit; Kumar, Vikas
Highlights: Higher reduction in α + β phase field leads to higher fatigue and dwell fatigue life. Higher reduction leads to finer constituents and higher basal orientation of grains. Higher hard orientation leads to higher dwell fatigue debit. The texture components in bar specimen is more basal, whereas off-basal in billet. Higher α + β reduction also results in more recrystallization. Abstract: In the present study, a near α titanium alloy, similar to IMI 834 alloy, was melted and thermo-mechanically processed. Different amount of deformation was imparted to the alloy in the α–β region and thereafter tensile, fatigue, and dwell fatigue properties were evaluated in a standard heat treatment condition. Higher α–β deformation resulted into a more refined microstructure. Further, based on EBSD analysis, it was found that higher α–β deformation led to a higher fatigue and dwell fatigue life, along with dwell fatigue life debit as compared to relatively lesser deformed specimen mainly due to hard (0 0 0 1) basal pole orientations, approximately, parallel to the loading axis.